Peran Sasi Negeri Terhadap Produksi Petani Kelapa di Negeri Tial Kecamatan Salahutu - Tutahey, Yuni S; Sopamena, Junianita F; FarFar, Risyart A (Jurnal Agrosilvopasture-Tech, 2025)
This research aims to determine the impact of sasi on the production of coconut farmers in Negeri Tial, Salahutu District. This research uses a qualitative descriptive research method. This research was conducted in Negeri Tial, Salahatu District. The sample in this research was 20 respondents. The data collection techniques used in the research were questionnaires, observation and documentation, with data analysis used being data reduction, data presentation and drawing conclusions. The research results show that 1) The role of Tial country's traditional institutions in managing Hamlet resources is carried out using the sasi system. The sasi system that is implemented affects the quality of coconut production, especially for coconut meat which has a rougher texture, thicker, has a savory taste with the oldest level of maturity, this has an impact on increasing coconut production. 2) The impact of sasi which is carried out in Negeri Tial, Salahutu District, can increase coconut productivity, thereby increasing the income of coconut farmers and expanding coconut sales locations outside the Ambon City area.